Stent-assisted Woven EndoBridge device for the treatment of intracranial aneurysms: an international multicenter study - Diestro, Jose Danilo Bengzon; Dibas, Mahmoud; Adeeb, Nimer; Regenhardt, Robert W.; Vranic, Justin E.; Guenego, Adrien; Lay, Sovann V.; Renieri, Leonardo; Balushi, Ali Al; Shotar, Eimad; Premat, Kévin; Namaani, Kareem El; et al. (Journal of neurosurgery, 2024)
OBJECTIVE: The Woven EndoBridge (WEB) device is an intrasaccular flow disruptor designed for wide-necked bifurcation aneurysms. These aneurysms may require the use of a concomitant stent. The objective of this study was to determine the clinical and radiological outcomes of patients undergoing stent-assisted WEB treatment. In addition, the authors also sought to determine the predictors of a concomitant stent in aneurysms treated with the WEB device. - METHODS: The data for this study were taken from the WorldWideWEB Consortium, an international multicenter cohort including patients treated with the WEB device. Aneurysms were classified into two groups based on treatment: stent-assisted WEB and WEB device alone. The authors compared clinical and radiological outcomes of both groups. Univariable and multivariable binary logistic regression analyses were performed to determine factors that predispose to stent use. - RESULTS: The study included 691 intracranial aneurysms (31 with stents and 660 without stents) treated with the WEB device. The adequate occlusion status did not differ between the two groups at the latest follow-up (83.3% vs 85.6%, p = 0.915). Patients who underwent stenting had more thromboembolic (32.3% vs 6.5%, p < 0.001) and procedural (16.1% vs 3.0%, p < 0.001) complications. Aneurysms treated with a concomitant stent had wider necks, greater heights, and lower dome-to-neck ratios. Increasing neck size was the only significant predictor for stent use. - CONCLUSIONS: This study demonstrates that there is no difference in the degree of aneurysm occlusion between the two groups; however, complications were more frequent in the stent group. In addition, a wider aneurysm neck predisposes to stent assistance in WEB-treated aneurysms.
Online veröffentlicht am 20. Oktober 2023
Gesehen am 04.03.2025